الرياضة في المنظور الإسلامي :‏ ‏المجالات والغايات /‏ - محروقى، سالم بن حمد بن سليمان
Sport is considered as one of the phenomenon of human society and one of the subjects which was focused upon. Accordingly, Islam has put great emphasis on sport to make the best of humans in a way that coexist with their instincts. However, the concept of sport in Islam is still shaped with vagueness and ambiguity. So this study tends to clarify the concept of sport in Islam, its purposes and the philosophy of sport that should be followed in the Islamic society in order to build a sport unit shined with a clear Islamic identity to contribute in confronting westernization of the Islamic culture and reduce the followship of current Muslim youths to the west (exporter/introducer/conveyer of modern sport). The study also tends to clarify the ways in which the Islamic world may benefit from sport in different aspects.In this study two methods are used to reach the facts and information, the historical method and the descriptive method. And data was collected from different participants (Islamic, educational and sports leaders as well as others who are concerned about sport in the sultanate of Oman and some other Islamic countries) through the use of personal interviews and questionnaires. The study reached some results such as: Sport is a humanitarian phenomena and is not restricted to some races and religions. Islam has put emphasis on sport and regulated it by setting some rules and conditions when practicing it such as using decent Islamic dress, prohibiting co practicing of sport (boys and girls together), avoid destructing oneself as well as others. There is a consistency between the Islamic perspective of sport and the global perspective. Therefore, it could be used to improve people physically, psychologically and socially as well as to develop the society economically and politically. The study strongly recommends islamizing sport and setting conditions for practicing it, deciding the proper way of practicing sport and the proper types of sports from the Islamic prospective. Besides, consideration should be given to school sports and give the sense of Islam to sport curriculum. Muslim preachers should use the sport world in preaching and should isolate themselves from sport world. Moreover, governments of the Islamic world should give more consideration to sport planning through having experts participating in the planning process from different aspects such as religious, educational, sport, economical, social and political to have sport impacts on all these aspects and being affected by them.